Smart Home Automation System Using IOT - Sheshalani Balasingam; Zapiee, Mohd Khuzaimi; Mohana, Dharnishaa (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
While the cost of living is going up, there is a growing focus to involve technology to lower those prices. With this in mind the Smart Home research allows the user to build and maintain a house that is smart enough to keep energy levels down while providing more automated applications. This concept can be suitably included to make our house smarter, saver, energy efficient and automated. This research focuses on building a save, automated system by using the internet connection that will smartly control the appliances like Lights, Fan, and other electrical appliances in our home. A smart home will take advantage of its environment and allow seamless control whether the user is present or away. This paper helps in saving the cost of electricity at home as well as saving the environment using wireless connections. With a home that has this advantage, you can know that your home is performing at its best in energy performance. By implementing this system, it is possible to explore a variety of different engineering challenges, including software programming arduino IDE, Wi-Fi, nodemcu, relay module, jumper wires and DC supply power. It can be control through smartphone. With prototype model, standard updates are basically a requirements. However, based on the result, this automation system provides great insights to the challenges of software and hardware design.